Sustainable solutions: exploring risks and strategies in Pakistan’s seafood trade for marine conservation - Mohsin, Muhammad; Yin, Hengbin; Mehak, Ana (Frontiers in Marine Science, 2024)
Global literature highlights risks in the seafood trade and suggests mitigation methods, but these issues are often overlooked in developing countries, particularly in Pakistan, due to ineffective policy implementation. This underlines the urgent need for a thorough investigation into Pakistan’s seafood trade to address its multifaceted risks and revive this agricultural sector. This study is notable for being the first to explore these uncharted risks in Pakistan’s seafood trade, which can help achieve the sustainable development goals (SDGs) of the United Nations, particularly SDG 14 (life underwater) and SDG 2 (zero hunger). Primary data were gathered from 626 respondents using snowball sampling and structured questionnaires from July 13, 2023, to December 27, 2023. The study used multi-criteria decision analysis, including fuzzy Analytic Hierarchy Process (AHP) and Importance Performance Analysis (IPA), and multivariate analysis, comprising Analysis of Moment Structures (AMOS), to analyze the data. The findings revealed that ‘environmental risks’ were the most significant, followed by ‘infrastructure and logistic risks’. The biggest sub-risk identified for managerial focus includes overfishing. Controlling overfishing is critical for ensuring marine conservation and reviving the seafood trade. Several sub-risks, like seafood prices, marketing strategies, consumer preferences, and tastes, are critical but never addressed in the regulations. Furthermore, risk perception mediates the relationship between risk management and risk performance. The survey respondents reported low-risk perception and inadequate management measures. Besides, this study expounds on ramifications, shortcomings, and areas for further research.